Material feminisms - Alaimo, Stacy, 1962-; Hekman, Susan J. (Indiana University Press, 2008)
Harnessing the energy of provocative theories generated by recent understandings of the human body, the natural world and the material world, 'Material Feminisms' presents a way for feminists to conceive of the question of materiality.